2016
DOI: 10.1016/j.apsusc.2016.08.083
|View full text |Cite
|
Sign up to set email alerts
|

Viscous surface flow induced on Ti-based bulk metallic glass by heavy ion irradiation

Abstract: a b s t r a c tTi-based bulk metallic glass was irradiated by a 20 MeV Cl 4+ ion beam under liquid-nitrogen cooling, which produced remarkable surface smoothing and roughening that respectively correspond to normal and off-normal incidence angles of irradiation. Atomic force microscopy confirms two types of periodic ripples distributed evenly over the rough glass surface. In terms of mechanism, irradiation-induced viscosity agrees with the theoretical prediction for metallic glasses near glass transition tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…However, it decreased to ~27 nm and ~24 nm in 1E12 and 1E13, respectively. Thus, AFM studies proved surface smoothening as the ion fluence increased, possibly because of irradiation-induced viscous flow in the sample, as explained by Zhang et al, on Ti-based bulk metallic glass by heavy ion irradiation [ 35 ]. Further, the mean surface roughness became reduced with an increasing 20 MeV Cl 4+ ion dose, which confirmed the smoothing of surfaces.…”
Section: Resultsmentioning
confidence: 97%
“…However, it decreased to ~27 nm and ~24 nm in 1E12 and 1E13, respectively. Thus, AFM studies proved surface smoothening as the ion fluence increased, possibly because of irradiation-induced viscous flow in the sample, as explained by Zhang et al, on Ti-based bulk metallic glass by heavy ion irradiation [ 35 ]. Further, the mean surface roughness became reduced with an increasing 20 MeV Cl 4+ ion dose, which confirmed the smoothing of surfaces.…”
Section: Resultsmentioning
confidence: 97%
“…The surface-confined viscous flow has been proven to play the dominant quantitative role during ion irradiation. This is caused by radiation-induced softening of the near-surface layer [11,23]. The origin of the softened region is caused by the rearrangements of atoms in certain structurally weak spots that behave as the liquid-like zone or the free volume.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies focus on the intrinsic irradiation responses by MGs, including damage morphology [6], enhanced mechanical performance [7], and local structure change [8,9]. Studies have shown that the ion beam resistance capability of MGs is better than either their corresponding crystalline counterparts or traditional radiation-resistant materials [10,11]. The entirely disordered structure is considered a desirable environment to relax the damage induced by radiation as well as local shear stress.…”
Section: Introductionmentioning
confidence: 99%
“…Bulk metallic glasses (MG) have attracted great interest in recent decades for its unique mechanical and chemical properties such as high strength, large elastic strain and high corrosion resistance [1][2][3][4][5][6]. Due to their inherent disordered structure, they are supposed to be ideal potential candidates for application in nuclear-irradiated environments or deep space.…”
Section: Introductionmentioning
confidence: 99%